Population Pharmacokinetic/Pharmacodynamic Modeling of Methylprednisolone in Neonates Undergoing Cardiopulmonary Bypass - Christoph P. Hornik; Daniel Gonzalez; Julie Dumond; Huali Wu; Eric M. Graham; Kevin D. Hill; Michael Cohen‐Wolkowiez (Wiley, 2019)
Methylprednisolone is used in neonates to modulate cardiopulmonary bypass (CPB)-induced inflammation, but optimal dosing and exposure are unknown. We used plasma methylprednisolone and interleukin (IL)‐6 and IL‐10 concentrations from neonates enrolled in a randomized trial comparing one vs. two doses of methylprednisolone to develop indirect response population pharmacokinetic/pharmacodynamic models characterizing the exposure-response relationships. We applied the models to simulate methylprednisolone dosages resulting in the desired IL‐6 and ‐10 exposures, known mediators of CPB‐induced inflammation. A total of 64 neonates (median weight 3.2 kg, range 2.2-4.3) contributed 290 plasma methylprednisolone concentrations (range 1.07-12,700 ng/mL) and IL‐6 (0-681 pg/mL) and IL‐10 (0.1-1125 pg/mL). Methylprednisolone plasma exposure following a single 10 mg/kg intravenous dose inhibited IL‐6 and stimulated IL‐10 production when compared with placebo. Higher (30 mg/kg) or more frequent (twice) dosing did not confer additional benefit. Clinical efficacy studies are needed to evaluate the effect of optimized dosing on outcomes.